Robust and adaptive control of coexisting attractors in nonlinear vibratory energy harvesters. (June 2018) - Haji Hosseinloo, Ashkan; Slotine, Jean-Jacques; Turitsyn, Konstantin
An immense body of research has focused on nonlinear vibration energy harvesting systems mainly because of the inherent narrow bandwidth of their linear counterparts. However, nonlinear systems driven by harmonic excitation often exhibit coexisting periodic or chaotic attractors. For effective energy harvesting, it is always desired to operate on the high-energy periodic orbits; therefore, it is crucial for the harvester to move to the desired attractor once the system is trapped in any other coexisting attractor. Here we propose a robust and adaptive sliding mode controller to move the nonlinear harvester to any desired attractor by a short entrainment on the desired attractor. The proposed controller is robust to disturbances and unmodeled dynamics and adaptive to the system parameters. The results show that the controller can successfully move the harvester to the desired attractor, even when the parameters are unknown, in a reasonable period of time, in less than 30 cycles of the excitation force.